Perception of human papillomavirus infection, cervical cancer and HPV vaccination in North Indian population. - Showket Hussain; Vilas Nasare; Malasha Kumari; Shashi Sharma; Mohammad Aijaz Khan; Bhudev C Das; Mausumi Bharadwaj (PLoS ONE, 2014)
Human Papillomavirus (HPV) -associated cervical cancer is the second-most common cancer in women worldwide but it is the most frequent gynaecological cancer and cancer associated death in India women. The objective of this study was to assess knowledge about cervical cancer, HPV, HPV vaccine, HPV vaccine acceptance among school and undergraduates students and their parent's perception about acceptance of HPV vaccine in Northern part of India (Delhi and NCR regions).A qualitative questionnaire based survey among 2500 urban/rural students aged 12-22 years was conducted.Overall, a low frequency (15%) of HPV and cervical cancer awareness was observed in students and their parents. However, the awareness was much higher in females belonging to urban setup compared to boys with a perception that HPV causes cervical cancer in women only. Additionally, only (13%) participants who were aware of cervical cancer and HPV) were willing to accept HPV vaccination. Apparently, parents of female students were two times more willing to accept HPV vaccination for their ward than male students (p<0.001; OR 95%CI = 2.09 (1.58-2.76).Cervical cancer and HPV awareness among school, undergraduate students and also to their parents was found to be very low in this part of India. The level of awareness and education appears to be insignificant determinants in rural compared to urban setup. Better health education will be needed to maximize public awareness for cervical cancer prevention.